Importance of rare case reports in medical literature - Luque, Andy H. (Revista Gregoriana de Ciencias de la Salud, 2025)
The presentation of atypical clinical cases, such as malignant granular cell tumors of the abdominal wall, is of great importance to the medical community. These reports expand our understanding of rare pathologies, providing essential information on their diagnosis, clinical characteristics, and therapeutic management. Given the limited availability of reports on abdominal wall locations and gastric locations, each additional case improves our understanding of these rare diseases.